1991
DOI: 10.1037/h0088239
|View full text |Cite
|
Sign up to set email alerts
|

Teacher ratings of social skills in popular and rejected males and females.

Abstract: Contrasted social competence differences between popular and rejected elementary-age students using the Social Skills Rating System (Gresham & Elliott, 1990), a standardized measure of social skills and interfering problem behaviors. Using the Coie, Dodge, and Coppotelli (1982) method of sociometric classification, 25 children were classified as Rejected and 24 students were classified as Popular out of an initial screening sample of 336 students in grades kindergarten through 6. Initial grade-level analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
2
6
0
1
Order By: Relevance
“…Prior research has shown connectedness to culturally different peers and to school to correlate positively with academic engagement and other prosocial activities that are condoned by adults (Battistich et al 2004;Henrich et al 2005;Karcher 2003;Karcher and Finn 2005;Thomas and Smith 2004). The two social skills on which elementary male mentees improvedempathy and cooperation-and the Hope scale also have been shown to predict academic engagement and improved interpersonal relationships (Elliott et al 1988;Shorey et al 2003;Stuart et al 1991). These findings, because of their relevance to success in school (both academically and interpersonally), seem to provide the most unequivocal support for the positive effects of SBM but only apply to elementary school boys.…”
Section: Discussionmentioning
confidence: 92%
“…Prior research has shown connectedness to culturally different peers and to school to correlate positively with academic engagement and other prosocial activities that are condoned by adults (Battistich et al 2004;Henrich et al 2005;Karcher 2003;Karcher and Finn 2005;Thomas and Smith 2004). The two social skills on which elementary male mentees improvedempathy and cooperation-and the Hope scale also have been shown to predict academic engagement and improved interpersonal relationships (Elliott et al 1988;Shorey et al 2003;Stuart et al 1991). These findings, because of their relevance to success in school (both academically and interpersonally), seem to provide the most unequivocal support for the positive effects of SBM but only apply to elementary school boys.…”
Section: Discussionmentioning
confidence: 92%
“…Construct validity has been reported a number of times (Merrell & Popinga, 1994;Stage, Cheney, Walker, & LaRocque, 2002;Stuart, Gresham, & Elliott, 1991). Reliability between teacher and parent ratings have also been evaluated (Fagan, & Fantuzzo, 1999;Merrell & Popinga, 1994;.…”
Section: The Social Skills Rating Systemmentioning
confidence: 99%
“…Sociometrically popular students demonstrate higher levels of sociability and cognitive abilities as compared with average students and are less aggressive and socially withdrawn (Newcomb et al, 1993). They achieve better results at school (Frentz et al, 1991) and have more developed social skills for reaching interpersonal goals and positive social relationships (Coie & Dodge, 1988;Stuart et al, 1991;Newcomb et al, 1993), choose topics for speaking that are viewed positively by their peers and have good conversational skills (Dygon et al, 1987) and have more positive self-concept, especially social self-concept, as compared to students from other sociometric groups (Boivin & Bégin, 1989;Jackson & Bracken, 1998). Differently, the correlates of peer perceived popularity are athletic ability, team membership, having money, making good grades, being fashionable and being physically attractive (Parkhurst & Hopmeyer, 1998).…”
Section: Introductionmentioning
confidence: 97%